2009
DOI: 10.1111/j.1467-9450.2009.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and serotonin systems modify environmental effects on human behavior: A review

Abstract: The relative influences of genetic and environmental factors in the development of human behavior have been a long-term topic for an intense debate. Recent behavioral genetic studies suggest focusing on the joint effect of genes and environment, and especially on the life-course developmental interplay between nature and nurture. Vulnerability to environmental adversities and sensitivity to its benefits may be conditional on genetic background, and regarding psychological outcomes, these kinds of gene · enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 71 publications
1
24
0
1
Order By: Relevance
“…In the light of the previous studies in behavior genetics, these results are not surprising, and very similar heritability estimates have been found for many other behavioral traits, such as personality, which probably originated in neuro-physiological differences between individuals [8]. Especially the role of dopamine and serotonin systems in the brain laying behind temperamental differences has been discussed [25], and the previous efforts to find candidate genes affecting temperament and personality differences have mainly focused on genes associated with these neuroregulatory systems [26, 27]. Previous genome-wide association studies of personality have not yielded many genes having significant effect on these traits, suggesting that each of the individual genes plays only a minor role in accounting for inter-individual differences, and that hundreds if not thousands of genes may be involved as has been found for intelligence [28].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the light of the previous studies in behavior genetics, these results are not surprising, and very similar heritability estimates have been found for many other behavioral traits, such as personality, which probably originated in neuro-physiological differences between individuals [8]. Especially the role of dopamine and serotonin systems in the brain laying behind temperamental differences has been discussed [25], and the previous efforts to find candidate genes affecting temperament and personality differences have mainly focused on genes associated with these neuroregulatory systems [26, 27]. Previous genome-wide association studies of personality have not yielded many genes having significant effect on these traits, suggesting that each of the individual genes plays only a minor role in accounting for inter-individual differences, and that hundreds if not thousands of genes may be involved as has been found for intelligence [28].…”
Section: Discussionsupporting
confidence: 67%
“…Very similar results have been found for other behavioral traits including disinhibition [10], substance use [13] and borderline personality [11]. There has been extensive research activity seeking to identify the molecular genetic background of these interactions focusing especially on genes associated with the serotonin neuroregulatory system [25], but the results are not conclusive so far. For example, Caspi et al [30] reported interaction between stressful life events and the polymorphisms of serotonin transporter gene 5-HTTLPR when predicting major depression in adulthood, but these findings have later been disputed [31].…”
Section: Discussionmentioning
confidence: 56%
“…MAOA has been implicated in affective functioning in knock-out mice suggesting that normal MAOA activity is important for anger expression [32]. Neurotransmitters 5-HT, NE and DA that MAOA metabolizes have been linked to depressive and substance abuse symptomatology [33] which are also outcomes predicted by child maltreatment [2, 3, 10, 3436]. …”
mentioning
confidence: 99%
“…These results, in concert with those from gene by environment studies (31,32), lend increasing support to the hypothesis that, rather than conferring susceptibility to psychopathology, polymorphisms at SLC6A4 and HTR2A enable increased plasticity of the serotonergic system in response to the social environment (31, 32) (SI Text: Haplotype Classification). This precludes a universal assumption of how SH1, SH2, HH1, and HH2 affect serotonergic functioning.…”
Section: Resultsmentioning
confidence: 68%